Kepemimpinan Transformasional dalam Implementasi Kurikulum Berbasis Cinta - Faishal Hafizh Ade Putra; Eka Mutia Sari Nur Hidayat; Ujang Miftahudin (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
The Love-Based Curriculum is an educational innovation developed to reinforce the values of compassion, empathy and respect for human dignity, as well as to foster character development in pupils as they face the various educational challenges of the 21st century. The successful implementation of this curriculum requires leadership from headteachers capable of mobilising the entire school community towards positive change. This study aims to analyse the role of transformational leadership in supporting the implementation of the Love-Based Curriculum in educational institutions. The study employs a qualitative approach using the library research method. Data were obtained through a review of various books, scientific journal articles, policy documents, and relevant previous research findings, and were subsequently analysed using content analysis techniques. The research findings indicate that transformational leadership makes a significant contribution to the implementation of the Love-Based Curriculum through four key dimensions: idealised influence, inspirational motivation, intellectual stimulation, and individualised consideration. These four dimensions are capable of fostering a school culture that is humanistic, inclusive and collaborative, whilst encouraging teachers to develop learning that is oriented towards the values of compassion, empathy and the character development of pupils. Furthermore, transformational leadership acts as a driving force in building commitment, innovation and synergy amongst the entire school community, thereby ensuring that the implementation of the Love-Based Curriculum can proceed effectively. Thus, transformational leadership is a strategic factor in realising an education system that fosters character, humanism and civility.